Farmers’ preferences for fertilizers derived from domestic sewage and kitchen waste – A discrete choice experiment in Germany - Utai, Katrin; Narjes, Manuel; Krimly, Tatjana; Lippert, Christian (Deutscher Fachverlag, 2022)
In view of increasing energy and resource scarcities, nutrient recycling from domestic wastewater is a promising way to obtain mineral fertilizers. Given the lacking evidence about the acceptance of recycling fertilizers by the farming sector, we elicited farmer preferences and willingness to pay (WTP) for selected attributes of mineral fertilizers made from domestic sewage and kitchen waste. We conducted a Discrete Choice Experiment with 206 German farmers and fitted a Random Parameter Logit (RPL) model. As-suming an average market price level of around 300 euros per tonne of N-P-K fertilizer, the choice exper-iment revealed that farmers not engaged in non-food production such as forage cultivation or renewable energies activities and without farmer-to-consumer direct marketing would accept a recycling fertilizer only together with a financial compensation via price discount of approximately 10%. The average WTP drops considerably if a fertilizer’s heavy metal contents are relatively high and if the absence of drug residues cannot be guaranteed, whereas a customizable nutrient composition and a constant supply availability would have a sales promoting effect. Farmers’ characteristics can only partly explain the notable heterogeneity of the WTP for the considered fertilizer attributes. Even though the WTP for a recycling fertilizer is on average less than that for a conventional mineral fertilizer, the estimated WTP standard deviations suggest that not all farmers expect a financial compensation via price discount when purchasing recycling fertilizers.